2020
DOI: 10.3390/biom10060894
|View full text |Cite
|
Sign up to set email alerts
|

Differential Anti-Proliferative and Anti-Migratory Activities of Ursolic Acid, 3-O-Acetylursolic Acid and Their Combination Treatments with Quercetin on Melanoma Cells

Abstract: We evaluate how 3-acetylation modulates the in vitro activity of ursolic acid in melanoma cells alone or in combination treatments with quercetin. Anti-proliferative studies on A375 cells and adult human dermal fibroblasts included analyses on cell cycle distribution, caspase activity, phosphatidylserine translocation, cell morphology and Bax/Bcl-2 protein expression. Then, 2D and 3D migration of B16F10 cells were studied using scratch and Transwell assays, respectively. Ursolic acid and 3-O-acetylursolic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Also, AUA (isolated or semi‐synthesized) revealed cytotoxic and cytostatic activity in vitro towards various cancer cells, i. e ., HL‐60, BGC‐823, Hela, Bel‐7402, HepG2, AGS, HELF, K562, A375 [41–43] . More in‐depth study on this compound was conducted by Alqathama et al [44] . who assessed anti‐migratory and pro‐apoptotic properties of AUA against A375 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Also, AUA (isolated or semi‐synthesized) revealed cytotoxic and cytostatic activity in vitro towards various cancer cells, i. e ., HL‐60, BGC‐823, Hela, Bel‐7402, HepG2, AGS, HELF, K562, A375 [41–43] . More in‐depth study on this compound was conducted by Alqathama et al [44] . who assessed anti‐migratory and pro‐apoptotic properties of AUA against A375 cells.…”
Section: Resultsmentioning
confidence: 99%
“…A similar or enhanced therapeutic potential has been reported with other structural ursolic acid derivatives such as amides, ester, and oxadiazole quinolone ( Mlala et al, 2019 ). 3-acetylursolic acid is a 3-acetylated derivative of ursolic acid, which has been reported to demonstrate similar potency and efficacy to ursolic acid when investigated for anti-proliferative and anti-migratory effects on melanoma cells ( AlQathama et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its anti-tumor effect is particularly prominent. The anti-tumor effect of UA has been reported in a variety of diseases, including breast cancer (31), leukemia (32), prostate cancer (33), melanoma (34), endometrial cancer (35), and lung cancer (36), among others. A large number of studies have shown that UA can inhibit tumor growth and metastasis by inhibiting tumor cell proliferation, invasion, and metastasis, and its mechanism is related to the expression of related genes on tumor cells, the oxidation of fatty acids increases, and the ability to synthesize fatty acids decreases.…”
Section: Discussionmentioning
confidence: 99%